Utility of the Swedish Anticholinergic Burden Scale in a memory clinic setting: a comparison with the Anticholinergic Cognitive Burden scale - Rube, Tanja; Londos, Elisabet; Johansson, Per ; 0000-0003-0073-7654 (Scientific Reports, 2026)
Anticholinergic burden is associated with cognitive impairment, especially in older individuals with neurodegenerative disorders such as Alzheimer’s disease. The objective of the study was to explore the use of drugs displaying anticholinergic properties and examine the utility of the newly developed Swedish Anticholinergic Burden Scale (Swe-ABS) in a memory clinic setting. A descriptive cross-sectional study, involving individuals ≥ 50 years of age attending a memory clinic in southern Sweden between September 2017 and September 2021. In total, 657 individuals, mean age 72.4 ± 9.0 years, 375 (57.1%) males, were included. The study population used 4805 medications at an average of 7.3 ± 4.3 per individual. A total of 448 (68.2%) participants used drugs with any anticholinergic effects identified with the Swe-ABS of whom 179 (27.2%) had a high anticholinergic burden (i.e., Swe-ABS ≥ 3). The corresponding figures for the established Anticholinergic Cognitive Burden (ACB) scale were 314 (47.8%) and 97 (14.8%) respectively. The mean Swe-ABS score was significantly higher than the mean ACB score (1.7 and 1.0; p < 0.05). Individuals < 75 years had a significant higher Swe-ABS score and ACB score than individuals ≥ 75 years (Swe-ABS: < 75 years: 1.94 ± 2.20 and ≥ 75 years: 1.50 ± 1.54; p < 0.05; ACB: < 75 years: 1.13 ± 1.57 and ≥ 75 years: 0.80 ± 1.14 p < 0.05). Within the study population, a total of 64 drugs not listed in the Swe-ABS were identified. This study highlights the prevalence of drugs with anticholinergic effects among individuals presumably vulnerable to muscarinic antagonism. The Swe-ABS, a risk scale for ascertaining the anticholinergic burden, seems to effectively identify a substantial proportion of drugs commonly used on the Swedish market. Trial registration ClinicalTrials.gov, TRN: NCT03208569, Registration date: 27 June 2017.